2022
DOI: 10.33549/physiolres.934854
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of WISP-1 (Wnt1-Inducible Signaling Pathway Protein 1) and Other Selected Adipokines in Children With Inflammatory Bowel Disease

Abstract: Wnt1 inducible protein-1 signaling pathway (WISP-1) is a relatively new adipokine involved in many cellular processes, including epithelial mucosa healing. The aim of the study was to compare circulating levels of WISP-1 and other selected adipokines [adiponectin, resistin and retinol-binding protein 4 (RBP-4)] in children with inflammatory bowel disease (IBD) with healthy controls and to investigate possible differences between Crohn's disease patients. (CD) or ulcerative colitis (UC). The study was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In Hispanic females, there was a lack of the typical postpubertal increase in adiponectin that is observed in non-Hispanic white females [74]. Another recently published study conducted by Karásková et al [75] reported that adiponectin was independently related to BMI in children. The authors also suggested that the adverse production of adipokines can represent the presence of dysfunctional fat tissue in IBD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hispanic females, there was a lack of the typical postpubertal increase in adiponectin that is observed in non-Hispanic white females [74]. Another recently published study conducted by Karásková et al [75] reported that adiponectin was independently related to BMI in children. The authors also suggested that the adverse production of adipokines can represent the presence of dysfunctional fat tissue in IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another recently published study conducted by Karásková et al [75] reported that adiponectin was independently related to BMI in children. The authors also suggested that the adverse production of adipokines can represent the presence of dysfunctional fat tissue in IBD patients.…”
Section: Color Version Available Onlinementioning
confidence: 94%
“…Other observations revealed significantly higher concentrations of resistin in pediatric IBD patients compared to the controls. What is more, a positive association between serum resistin and fecal calprotectin together with both CRP and white blood cell count has been noted as well [ 135 , 136 ].…”
Section: Resistin—a Significant Marker Of Systemic Inflammationmentioning
confidence: 99%
“…Regulatory immune function has been identified in many of them. The role of several adipokines in intestinal inflammation has recently been investigated [ 4 , 15 , 16 ]. The significance of vitamin D deficiency on abnormal production of adipokines in patients with IBD remains unclear.…”
Section: Introductionmentioning
confidence: 99%